Efeito da minociclina sobre a microglia do Locus coeruleus em um modelo esporádico para Doença de Alzheimer - Paneghini, Julia de Lima (2022)
Alzheimer's disease (AD) is the most common neurodegenerative dementia in the world. Inflammation of the central nervous system in AD is the result of the activation of micróglia cells in response to the formation of amyloid plaques and / or hyperphosphorylation of the tau protein (NFTs), which can promote a chronic state of neuroinflammation that worsens and accelerates the progression of disease. In our previous study, we demonstrated the increased expression of beta amyloid peptide in the Locus Coeruleus (LC) in a sporadic AD model induced by intracerebroventricular injection of 2 mg / kg of streptozotocin (STZ). LC is a region that can trigger the initial neuroinflammatory process in AD. Thus, we investigated whether treatment with minocycline (micróglia inhibitor) would affect micróglia cells in the LC in rats treated with STZ. Control or STZ Wistar rats were treated for 5 consecutive days with minocycline (30 mg/kg, ip) or vehicle. After 5 days of treatment, the animals were submitted to the Barnes Maze behavioral test and immunohistochemistry was performed for LC micróglia by labeling with Iba-1. Regarding the Barnes test, we did not observe a significant difference in the number of hits in the target hole between animals in the Vehicle group, treated with Placebo or Minocycline (Vehicle-Control: 6.6 ± 2.9 vs Vehicle-Minocycline: 6.4 ± 3.1; P > 0.05). The STZ animals had a lower number of hits in the target hole than their respective vehicles (p< 0.05). We observed that the STZ-Minocycline group had a higher number of hits in the target hole than the STZ-Control group (STZ-Mino: 3.8 ± 2.9 vs STZ-Placebo: 2.2 ± 1.1; p< 0.05). We observed that the treatment with minocycline decreased the micróglia cell density in the AD model (p<0.05) and the treatment did not alter the proximity of the micróglia cells in the STZ model (p> 0.05). Likewise, after treatment with minocycline, the arborization of cells in the STZ-AD group increased (p <0.05) and the cell body decreased (p <0.05), indicating the return of the micróglia to its reactive form. We also observed a decrease in the morphological index (p<0.05), which reflects the inactivation of micróglia cells in the AD model. Our data suggest that minocycline reduced cognitive impairment, which is possibly associated with inhibition of LC micróglia.